Answer:
Answer:
x = \dfrac{2}{5} + \dfrac{\sqrt{14}}{5}x=
5
2
+
5
14
or x = \dfrac{2}{5} - \dfrac{\sqrt{14}}{5}x=
5
2
−
5
14
Step-by-step explanation:
5x^2 - 2 = 4x5x
2
−2=4x
5x^2 - 4x - 2 = 05x
2
−4x−2=0
x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a}x=
2a
−b±
b
2
−4ac
x = \dfrac{-(-4) \pm \sqrt{(-4)^2 - 4(5)(-2)}}{2(5)}x=
2(5)
−(−4)±
(−4)
2
−4(5)(−2)
x = \dfrac{4 \pm \sqrt{16 + 40}}{10}x=
10
4±
16+40
x = \dfrac{4 \pm 2\sqrt{14}}{10}x=
10
4±2
14
x = \dfrac{2 \pm \sqrt{14}}{5}x=
5
2±
14
x = \dfrac{2}{5} + \dfrac{\sqrt{14}}{5}x=
5
2
+
5
14
or x = \dfrac{2}{5} - \dfrac{\sqrt{14}}{5}x=
5
2
−
5
14